2015
DOI: 10.2147/dhps.s50549
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of hormone therapy for prostate cancer

Abstract: Androgen deprivation therapy (ADT) has been the mainstay of treatment for advanced prostate cancer for decades, and has been shown to control disease and improve symptoms. In addition, for men with high-risk localized or locally advanced prostate cancer, short-course ADT in combination with radiotherapy improves survival. There is evidence that ADT increases cardiovascular risk, particularly in men with preexisting cardiovascular disease. This increased risk may apply even with short-course ADT. In an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…Our results show a negative association between concentrations of T/DHT and cholesterol subfractions, and this confirms previous outcomes suggesting that increased concentrations of T/DHT lead to decreased concentrations of total cholesterol and LDL cholesterol [ 6 ]. Similar trends in the relationships between total cholesterol or LDL cholesterol and T concentrations have been observed in hypogonadal men treated with T/DHT replacement therapy [ 4 ]. This further confirms that T/DHT may have a beneficial impact on lipid profile, even in subjects not receiving hormonal replacement therapies.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our results show a negative association between concentrations of T/DHT and cholesterol subfractions, and this confirms previous outcomes suggesting that increased concentrations of T/DHT lead to decreased concentrations of total cholesterol and LDL cholesterol [ 6 ]. Similar trends in the relationships between total cholesterol or LDL cholesterol and T concentrations have been observed in hypogonadal men treated with T/DHT replacement therapy [ 4 ]. This further confirms that T/DHT may have a beneficial impact on lipid profile, even in subjects not receiving hormonal replacement therapies.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, some men undergoing androgen deprivation therapy due to prostate cancer present an increased risk of impaired glucose and/or lipid metabolism, often contributing to cardiovascular ischaemic events [ 4 ]. This implies that T may be somehow involved in carbohydrate and lipid metabolism and thus, may indirectly contribute to the ongoing onset of atherogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies assess the occurrence of cardiovascular adverse events in patients with prostate cancer on androgen deprivation therapy [13][14][15][16][17], but data regarding the risk of sudden cardiac death in these patients are inconclusive. An analysis of the Surveillance, Epidemiology and End Results Medicare database which includes 73,196 patients with locoregional prostate cancer showed that the use of gonadotropin-releasing hormone receptor agonists was associated with a higher risk of coronary heart disease, sudden cardiac death, and myocardial infarction compared to orchiectomy [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The adipose tissue accumulates mainly subcutaneously without changes in waist-hip ratio. ADT can also induce fatal ventricular arrhythmia by lengthening Q-T interval on ECG [ 38 , 39 , 40 ] due to hypogonadism but also by a direct effect on I k currents in myocardial cells, described experimentally for some ADT [ 38 ] ( Figure 3 ). ADT raises the thrombotic risk by increasing the serum level of fibrinogen, as demonstrated by Ziaran et al [ 41 ] in 97 patients with locally advanced prostate cancer after 12 months of treatment, but not the serum level of CRP [ 16 , 42 ].…”
Section: Cardiovascular Effects Of Adtmentioning
confidence: 99%